WS2/p-Si-based photocathodes with high activity originated from the unique vertical geometry of the 2D WS2 nanoplatelets - Patel, Malkeshkumar; Nguyen, Thanh Tai; Kim, Jina; Kim, Joondong; Kim, Yu Kwon (FlatChem, 2022)
Earth-abundant two-dimensional (2D) materials-based photocathodes for solar hydrogen production may replace conventional noble metal-based ones when they can be grown with a proper orientation and dimension for efficient charge transfer and catalytic reactions. Here, we show that WS2 films can be grown as wafer-scale films with unique vertically aligned 2H-WS2 nanoplatelets using a single-step vacuum deposition process directly on substrates such as Si wafer and F-doped tin oxide (FTO)/glass. The as-grown WS2/p-Si shows enhanced photocathode performances that are attributed to the unique vertical WS2 nanoplatelet structure, which endows excellent antireflection properties (reflectance as low as ∼ 4%) for enhanced absorption, high photocurrent density (ca. 37 mA cm−2) at low overpotential optimized by controlled vertical length, and catalytically active WS2 edge-sites exposed to the surface for excellent catalytic hydrogen evolution reaction (HER). The results suggest that the nanostructured WS2/p-Si heterostructures are promising multi-functional photocathodes for solar hydrogen production with excellent stability for long-term operation in ambient condition.
Keywords: Edge exposed electrocatalyst; Solar hydrogen generation; Water splitting; WS2 nanoplatelets; WS2/p-Si photocathode